STEREOCHEMICAL INDUCTION IN THE GENERATION OF 1-CHLORO-1-PHENYL-2-NEOPENTYLSILENE - YOO, BR; JUNG, IN; LEE, ME; KIM, CH (KOREAN CHEMICAL SOC, 1991)
The reaction of dichlorophenylvinylsilane with tert-butyllithium in hydrocarbon solvents at room temperature or below generated the Z and E-isomers of 1-chloro-1-phenyl-2-neopentylsilene. The intermediates were trapped by cyclopentadiene, anthracene and methoxytrimethylsilane to give a consistent 90/10 ratio for the Z-silene to E-silene adduct. This result was interpreted as an evidence for stereochemical induction in the silene generation reaction.
Keywords: SILENE STEREOCHEMISTRY; ALPHA-LITHIOSILANES; "1-METHYL-1-PHENYL-2-NEOPENTYLSILENE